2020
DOI: 10.22271/chemi.2020.v8.i1ae.8568
|View full text |Cite
|
Sign up to set email alerts
|

Studies on heterosis for yield and yield attributing traits in American cotton (<em>Gossypium hirsutum</em> L.)

Abstract: The present study was made in upland cotton with 10 x 10 half diallel to assess the extent of heterosis over standard check (LAHH 5) for seed cotton yield and its related traits at Regional Agricultural Research Station, Lam, Guntur. The highest heterotic effect were recorded in the hybrids SCS-1207 × GSHV-177, GSHV-177 × L1231 and SCS-1207 × PBH-13 were promising hybrids in this study over the standard check for seed cotton yield per plant and its most of the yield attributing traits. Those hybrids exhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
0
0
Order By: Relevance
“…Significant standard heterosis for UHML was observed in the hybrid SVPR6 x DB1602 (20.54 %) and for bundle strength in SVPR6 x DB1602 (13.24 %). The highest expression of heterosis by most of the hybrids for the number of bolls per plant, seed cotton yield per plant and boll weight is in accordance with the results of Soomro et al (2009), Eswari et al (2016), Gohil et al (2017), Naik et al (2020) and Kirthika et al (2020) The estimates of gca effects of parents for yield and fibre quality traits were listed in Table 4. An overall assessment of general combining ability effects manifested that CO16 and MCU7 among the lines were good and uniform general combiners for seed cotton yield and its contributing traits and for fibre quality the best combiner was SVPR 6.…”
Section: Resultssupporting
confidence: 88%
“…Significant standard heterosis for UHML was observed in the hybrid SVPR6 x DB1602 (20.54 %) and for bundle strength in SVPR6 x DB1602 (13.24 %). The highest expression of heterosis by most of the hybrids for the number of bolls per plant, seed cotton yield per plant and boll weight is in accordance with the results of Soomro et al (2009), Eswari et al (2016), Gohil et al (2017), Naik et al (2020) and Kirthika et al (2020) The estimates of gca effects of parents for yield and fibre quality traits were listed in Table 4. An overall assessment of general combining ability effects manifested that CO16 and MCU7 among the lines were good and uniform general combiners for seed cotton yield and its contributing traits and for fibre quality the best combiner was SVPR 6.…”
Section: Resultssupporting
confidence: 88%
“…Micronaire value negatively correlated with fiber maturity. Naik et al (2019) lint index (g), micronaire value and uniformity ratio were found to have significant positive association with seed cotton yield plant -1 .…”
Section: Discussionmentioning
confidence: 92%
“…Overall, the majority of the hybrids manifested low magnitude of heterosis for ginning out-turn than their parents. Other studies reported negative heterosis over mid parent and better parent in intra G. hirsutum L. hybrids (Soomro et al, 2016;Monicashree et al, 2017;Naik et al, 2020). Similarly, Gohil et al (2017 and Malathi et al (2019) reported heterosis over mid parent and better parent towards negative direction in interspecific hybrids.…”
Section: International Journal Of Agricultural and Applied Sciences 1(1)mentioning
confidence: 88%